2008
DOI: 10.1177/0267659108100457
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon pumping increases renal blood flow in patients with low left ventricular ejection fraction

Abstract: Intra-aortic balloon pumping (IABP) has, for decades, been one of the key treatment modalities following impaired cardiac function after cardiac surgery. IABP increases cardiac output, decreases oxygen consumption of the heart and relieves the left ventricle. However, a number of complications have been reported in connection with IABP treatment. Only a few studies have evaluated renal blood flow and the purpose of this prospective study was to evaluate whether renal blood flow was affected by IABP treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
3
10
1
Order By: Relevance
“…Moreover, we confirmed that IABP increased renal flow (Sloth et al., ), and this improvement occurred without any difference between the right and left kidneys despite their different anatomical features. However, it is known that there are no differences in diameter or distances to branching between the right and left renal arteries (Tarzamni et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we confirmed that IABP increased renal flow (Sloth et al., ), and this improvement occurred without any difference between the right and left kidneys despite their different anatomical features. However, it is known that there are no differences in diameter or distances to branching between the right and left renal arteries (Tarzamni et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…This is an interesting clinical observation that received less attention in previous reports about IABP in non-ischaemic CS. One study on ultrasound spectral Doppler estimation of renal flow velocity reported higher renal blood flow during IABP support [22]. Although we did not routinely perform haemodynamic measurements in the present study, we hypothesize that the decrease in LV afterload by IABP increases right to left flow and leads to decreased right-sided congestion and increased renal perfusion, which result in enhanced diuresis.…”
Section: Discussionmentioning
confidence: 76%
“…In agreement with this, a non-significant higher blood flow in the carotid artery was observed during combined support compared to the Impella® device alone. Only a few studies have investigated the effect of IABP on renal blood flow with conflicting results, demonstrating both increased and unchanged renal blood flow during IABP support [22,23]. However, whether the higher blood flow during Impella® support was associated with an improved kidney function is unknown.…”
Section: Discussionmentioning
confidence: 99%